2017
DOI: 10.18632/oncotarget.19847
|View full text |Cite
|
Sign up to set email alerts
|

3D modeling of cancer stem cell niche

Abstract: Cancer stem cells reside in a distinct microenvironment called niche. The reciprocal interactions between cancer stem cells and niche contribute to the maintenance and enrichment of cancer stem cells. In order to simulate the interactions between cancer stem cells and niche, three-dimensional models have been developed. These in vitro culture systems recapitulate the spatial dimension, cellular heterogeneity, and the molecular networks of the tumor microenvironment and show great promise in elucidating the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 184 publications
(199 reference statements)
0
40
0
1
Order By: Relevance
“…When cultured as single cells into matrigel [30][31][32] the L1 low cells generated more organoid-like structures than L1 high cells ( Fig. 2c) and retained low expression of L1 even after 7 days of culture (Org) ( Supplementary Fig.…”
Section: Lack Of L1cam Expression Features Factors Associated With Stmentioning
confidence: 99%
“…When cultured as single cells into matrigel [30][31][32] the L1 low cells generated more organoid-like structures than L1 high cells ( Fig. 2c) and retained low expression of L1 even after 7 days of culture (Org) ( Supplementary Fig.…”
Section: Lack Of L1cam Expression Features Factors Associated With Stmentioning
confidence: 99%
“…To this end, we used as an experimental model the generation and maintenance of oncospheres starting from breast cancer cells. These structures can be generated with multiple cancer cell lines and are known to be enriched in CSCs, on the basis of the expression of CSC genes, including ALDH1 , SOX2 , CD44+/CD24− [14,15]. They are also enriched in markers of EMT, including CTNNB1 , EGR1 , ERBB2 and MUC1 [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly though, EGF is also a known epithelial differentiation factor; however, this effect seems to be successfully counteracted by other components of the stem medium as evident by the expression profiles of the SCESM spheroids [ 55 ]. The SCESM spheroids exceeded 450 µm already at day 3 and 800 µm at day four (these diameters enabling the development of hypoxia and necrotic core, respectively) [ 28 , 56 , 57 ], both stimulating the dedifferentiation process and CSC enrichment [ 30 , 58 , 59 , 60 ]. Additionally, analyses of the proliferation marker Ki-67 and the 7-AAD nuclear stain suggested that only the outermost rim of cells is fast proliferating, while the cells deeper in are poorly/not proliferating.…”
Section: Discussionmentioning
confidence: 99%